Spatial Bricolage: The Art of Poetically Making Do - Les Roberts (Humanities, 2018)
This paper provides an introductory overview to the Humanities special issue on ‘spatial bricolage’. The individual contributions that make up the special issue are outlined and salient themes pulled out that address and respond to some the wider discussion points raised throughout this introduction. These are closely focused around the central concept of bricolage and the idea of the researcher as bricoleur. Some background context on the anthropological underpinnings to bricolage is provided, alongside methodological reflections that relate the concept to ideas of ‘gleaning’ as a creative and performative engagement with everyday spaces as they are ‘found’ and rehearsed in practice. A core focus on questions of method, and of autoethnographic approaches in particular, is presented alongside questions of research ethics and the policing thereof by institutional structures of disciplining and audit in the neoliberal academy. It is argued that bricolage is, among other things, a practical response to a field of practice that at times constrains as much as it allows space to roam, unimpeded, across disciplinary boundaries. From the overarching purview of spatial humanities and spatial anthropology, it is shown that discussions of bricolage and the researcher as bricoleur can help make explicit the poetics and affects of space, as well as the ethical and procedural frameworks that are brought to bear on how space is put into practice.